Evidence for Status Epilepticus and Pro-Inflammatory Changes after Intranasal Kainic Acid Administration in Mice - Sabilallah, Mounira; Fontanaud, Pierre; Linck, Nathalie; Boussadia, Badreddine; Peyroutou, Ronan; Lasgouzes, Thibault; Rassendren, François A.; Marchi, Nicola; Hirbec, Helene E. (PLOS ONE, 2016)
Kainic acid (KA) is routinely used to elicit status epilepticus (SE) and epileptogenesis. Among the available KA administration protocols, intranasal instillation (IN) remains understudied. Dosages of KA were instilled IN in mice. Racine Scale and Video-EEG were used to assess and quantify SE onset. Time spent in SE and spike activity was quantified for each animal and confirmed by power spectrum analysis. Immunohistochemistry and qPCR were performed to define brain inflammation occurring after SE, including activated microglial phenotypes. Long term video-EEG recording was also performed. Titration of IN KA showed that a dose of 30 mg/kg was associated with low mortality while eliciting SE. IN KA provoked at least one behavioral and electrographic SE in the majority of the mice (>90%). Behavioral and EEG SE were accompanied by a rapid and persistent microglial-astrocytic cell activation and hippocampal neurodegeneration. Specifically, microglial modifications involved both pro- (M1) and anti-inflammatory (M2) genes. Our initial long-term video-EEG exploration conducted using a small cohort of mice indicated the appearance of spike activity or SE. Our study demonstrated that induction of SE is attainable using IN KA in mice. Typical pro-inflammatory brain changes were observed in this model after SE, supporting disease pathophysiology. Our results are in favor of the further development of IN KA as a means to study seizure disorders. A possibility for tailoring this model to drug testing or to study mechanisms of disease is offered.